Pengaruh Pengalaman Menginap Berbasis Alam Terhadap Kepuasan Tamu Di Imelda Resort Air Manis Padang - Rafinas Rafinas; Pasaribu Pasaribu; Dendy Rully Putra (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
This study aims to analyze nature-based stay experiences, guest satisfaction levels, and the influence of nature-based stay experiences on guest satisfaction at Imelda Resort Air Manis Padang. This research employed a quantitative approach using a causal associative method. The population consisted of 1,728 guests, and a sample of 95 respondents was selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive analysis, simple linear regression, the t-test, the F-test, and the coefficient of determination test using SPSS version 27. The findings indicate that both nature-based stay experiences and guest satisfaction were categorized as good. The results also reveal that nature-based stay experiences have a positive and significant effect on guest satisfaction, contributing 52.3%, while the remaining percentage is influenced by other factors beyond the scope of this study. These findings suggest that nature-based stay experiences play an important role in enhancing guest satisfaction at Imelda Resort Air Manis Padang.